A bibliometric and visual analysis of Jak1 to explore trends and frontiers - Yu, Cong; Cao, Jiamin; Xie, Xiaodong; Chen, Wenguang; Hong, Ensi (Frontiers in Oncology, 2025)
BackgroundJAK1, a member of the JAK kinase family, is involved in the signal transduction of multiple cytokine pathways and is crucial in the onset and progression of inflammation and tumours. Consequently, JAK1 has garnered significant attention in recent years.MethodsWe use bibliometric and visual analysis to evaluate the thematic trends and knowledge structure of TRPV1’s research papers on JAK1, sourced from the Web of Science core collection from 2003 to 2024. CiteSpace is used to analyze references and keywords of authors, institutions, countries, and commonly cited, and applies co-current and clustering functions to generate visual knowledge maps.ResultsA total of 3,686 articles were incorporated. The primary research domain of JAK1 is oncology; the United States leads in publication volume, with the University of Texas holding the most prominent central position. The keyword distribution indicates that the literature on JAK1 from 2003 to 2009 primarily concentrated on mechanistic studies, encompassing gene expression, activation, pathways, and cell apoptosis. From 2008 to 2018, research hotspots predominantly examined the association between JAK1 and various disease atlases. Beginning in 2012 and extending to 2024, the focus shifted towards the research and development of clinical pharmaceuticals, along with their safety and efficacy. Gene expression, signal transduction, atopic dermatitis, and JAK1-selective inhibitors have emerged as prominent research areas in recent years, exhibiting significant potential for development.ConclusionThis study presents the contemporary status and prospective trends of JAK1 research over the last two decades. Current research focuses on skin inflammation, rheumatoid arthritis, and tumor-related diseases, while new signaling pathways are constantly being discovered. JAK1 inhibitors are gradually being used in clinical practice and have good development prospects, which will become the main trend of future research.